Cognitive behavioural group therapy for treatment of addictive smoking - Yeşildal, Anıl; Oğuz, Gülay; Güven, Mükerrem; Sungur, M.Zihni; Üstünuçar, İlknur (Journal of Dependence, 2014)
Objective: Smoking is a serious unresolved public health problem. Allen Carr Method can be an attractive option for the smokers who want to quit smoking. This method might be admittable as cognitive-behavioral oriented group psychotherapy because the target is to reorganize the defective coding about cigarette. In this method it is assumed that to control the effects of psychological addiction will enable to quit smoking. The aim of this study is to research the effectiveness of Allen Carr method during quitting smoking process in long term. Method: 130 volunteer smokers participated to the study. Fagerström Test for Nicotine Dependence Early Warning and Glad Non-Smoker Questionnaires were applied at the 3rd day, 1st month and 1st year to evaluate adaptation to a smoke free life. Results: At the end of one year 28-62% success ratio has been founded in different groups. Conclusion: As a conclusion this method is an effective option for treatment of cigarette use disorder. Allen Carr method, which resolves psychological dependence of nicotine, might be considered to be an important alternative to pharmacological treatments. Further randomized controlled studies are required to conclude the efficiency of the method.